2018
DOI: 10.1111/anae.14526
|View full text |Cite|
|
Sign up to set email alerts
|

Paediatric intensive care and neonatal intensive care airway management in the United Kingdom: the PICNIC survey

Abstract: We would like to comment on, and correct some misunderstandings in, the paper by Foy et al., which suggests that there are major gaps in optimal airway management in neonatal intensive care units (NICUs) in the UK, particularly lack of continuous waveform capnography and/or videolarygoscopy [1]. We are in full agreement with the NHS Improvement recommendation that undetected oesophageal intubation should be a 'Never Event', but note that detection of this event relates mostly to the use of capnography at intub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Studien bei Erwachsenen legen nahe, dass eine quantitative Kapnographie beim Nachweis des etCO 2 empfindlicher sein kann als eine kolorimetrische Bestimmung. Da jedoch keine Validitätsdaten zur Haupt- oder Nebenstrommessung bei Neugeborenen vorliegen, ist bei der Verwendung einer quantitativen Kapnographie Vorsicht geboten [ 265 , 267 , 268 ].…”
Section: Wissenschaftliche Grundlagen Auf Deren Basis Die Empfehlungen Für Die Praxis Zur Versorgung Und Reanimation Des Neugeborenen Berunclassified
“…Studien bei Erwachsenen legen nahe, dass eine quantitative Kapnographie beim Nachweis des etCO 2 empfindlicher sein kann als eine kolorimetrische Bestimmung. Da jedoch keine Validitätsdaten zur Haupt- oder Nebenstrommessung bei Neugeborenen vorliegen, ist bei der Verwendung einer quantitativen Kapnographie Vorsicht geboten [ 265 , 267 , 268 ].…”
Section: Wissenschaftliche Grundlagen Auf Deren Basis Die Empfehlungen Für Die Praxis Zur Versorgung Und Reanimation Des Neugeborenen Berunclassified
“…Although interpreted by mainstream media and the British Medical Journal as a potential shortcoming,14 the evidence for the superiority of waveform capnography over transcutaneous capnometry (common in neonates, perhaps due to their comparatively thinner skin) in neonatal practice is less convincing. A British Association of Perinatal Medicine working group has recently commented on the survey by Foy et al 15. A survey of NICUs in Germany, Switzerland and Austria by Rüdiger et al 8 found that 95% of NICUs used TCCO 2 8…”
Section: Commentarymentioning
confidence: 99%
“…In response to the editorial by Cook and Harrop-Griffiths on capnography,1 we reiterate the British Association of Perinatal Medicine’s position statement on waveform capnography in newborn infants2 published in response to the article by Foy et al in Anaesthesia 3…”
mentioning
confidence: 99%